2016
DOI: 10.1111/1440-1681.12602
|View full text |Cite
|
Sign up to set email alerts
|

The role of Toll‐like receptor 4 (TLR4) in cardiac ischaemic‐reperfusion injury, cardioprotection and preconditioning

Abstract: Cardiac ischaemic-reperfusion injury (IRI) remains the primary cause of mortality throughout the developed world. Molecular mechanisms underlying IRI are complex and are often interlinked with each other driving a synergistic response. Toll-like receptor 4 (TLR4), an immunosurveillance receptor, is known to enhance tissue injury during IRI by enhancing the inflammatory response. The release of endogenous components during IRI bind onto TLR4 leading to the activation of multiple signalling kinases. Once this ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 84 publications
(142 reference statements)
2
22
0
Order By: Relevance
“…Class Ia DAMPs such as HMGB1 and HSPs are generated in reperfusion‐injured organs including human renal allografts , but also emitted under BD conditions . These molecules considerably contribute to creation of sterile inflammation including IRI‐mediated inflammation when sensed by those members of the NLR or ALR family that form inflammasomes .…”
Section: A Plethora Of Damps and An Attempt To Classify Themmentioning
confidence: 99%
“…Class Ia DAMPs such as HMGB1 and HSPs are generated in reperfusion‐injured organs including human renal allografts , but also emitted under BD conditions . These molecules considerably contribute to creation of sterile inflammation including IRI‐mediated inflammation when sensed by those members of the NLR or ALR family that form inflammasomes .…”
Section: A Plethora Of Damps and An Attempt To Classify Themmentioning
confidence: 99%
“…The present study showed that TNC increased TLR4 expression and promoted NF-κB translocation from cytoplasm to nucleus of cardiomyocytes with H/R injury, which is dependent on IκBα. In response to MI, TLR4 is activated and induce cardiomyocytes express proinflammatory cytokines and initiate a local inflammatory response [6]. TLR4 induced the NF-κB dependent expression of proinflammatory cytokines, such as TNF-α,IL-1β IL-6 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4) is a primary receptor of the innate immune system and can induce inflammatory response in myocardial ischemia through activating signaling pathways, like nuclear factor kappa B (NF-κB) [6]. Activation of NF-κB promotes production of proinflammatory cytokines, such as interleukin 1β (IL-1β) and tumor necrosis factor-α (TNF-α) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TLRs discriminate between “self” and “non-self” and activate the innate immune inflammatory response [ 25 ]. TLRs, mainly TLR2 and TLR4, have been shown to be associated with cardiovascular disease, as well as with cardioprotection afforded by different interventions [ 26 , 27 ]. It is well-documented that inflammation via TLR-mediated MyD88-dependent NF-κB activation plays an important cytoprotective role in myocardial I/R injury [ 28 ], whereas TLR4 is also associated with cardioprotection by the activation of PI3K/Akt signaling, suggesting that there is a crosstalk between TLR and PI3K/Akt pathways in myocardial I/R injury and cardioprotection [ 29 ].…”
Section: Introductionmentioning
confidence: 99%